Audit Zakat Research: A Bibliometic Analysis - Taqi, Muhamad; Sabaruddinsah, Sabaruddinsah; Rusydiana, Aam Slamet (Univeristas Islam Bandung, 2022)
This research aims to find out the trend of the development of research maps with the theme of zakat audit published by reputable journals related to Islamic economics and finance. There were 113 indexed research publications analyzed in this study. Then the data was processed and analyzed using R Bliblioshiny software to find bibliometric maps related to economic development and Islamic finance in zakat audit research. It was found that the publication of research related to the theme experienced a significant increase, and the majority of documents were in the form of journal articles. The most famous author is Sofyani H, and the most popular keyword topics are zakat and accounting. The contribution of this research is expected to be able to strengthen the transparency and accountability of the public social sector in this case the zakat institution so as to increase public trust.